The Role of Principal Leadership and Work Stress on Teacher Work Commitment - Siti Elsha Fauziah; Suryadi Suryadi; Siti Zulaikha (STAI Hubbulwathan Duri, 2021)
This study aims to determine the effect of principal leadership and work stress on the work commitment of extraordinary school teachers in North Jakarta. The method in this research uses a quantitative approach to multiple linear regression models. A sample test was conducted on 104 teachers of extraordinary schools in North Jakarta using the Slovin formula. Hypothesis testing is obtained from the t-test and the F-test. The results show that leadership has a positive and significant role in work commitment; job stress has a negative and effect on the work commitment where increased work stress will decrease teacher work commitment. Leadership and work stress affect the work commitment of teachers at special schools in North Jakarta with a coefficient of determination of 0,357 or 35,7%, meaning that leadership and work stress simultaneously affect teacher work commitment by 35.7%.